Implant failure in a proximal femoral fracture treated with dynamic hip screw fixation - Dabis, John (J Surg Case Rep, 2015)
Dynamic hip screw fixation is a common orthopaedic procedure and to date, still can cause difficulties to the senior trauma surgeon. We present a case where an extra-capsular fracture of the proximal femur was managed with a dynamic hip screw (DHS) fixation. She proceeded to the operating theatre, where the fracture was stabilized with a 75-mm DHS and short-barrelled plate. The implant position was checked with intraoperative screening and the position accepted. Following attempted mobilization at 11 days post-operatively, the patient developed a recurrence of her preoperative pain. X-ray showed that the implant screw had separated from the barrel. Later scrutiny of the intraoperative screening films revealed that the barrel and screw were not engaged at the time of surgery. Intraoperative screening films should be carefully checked to ensure congruity of implant components.